Soviet women - everyday lives - Ilič, Melanie, 1962- (Abingdon, Oxon)
1 online resource.
Keywords: Based on an extensive reading of a broad range of women's accounts of their lives in the Soviet Union, this book focuses on many hidden aspects of Soviet women's everyday lives, thereby revealing a great deal about how the Soviet Union operated on a day-to-day basis and about the place of the individual within it. Including testimony from both celebrated literary and cultural figures and from many ordinary people, and from both enthusiastic supporters of the regime and dissidents, the book considers women's daily routines, attitudes and behaviours. It highlights some of the hidden inequalities of an ostensibly egalitarian society, and considers many wider questions, including how extensive was the reach' of the Soviet regime; how modern' was it; how far were there continuities after 1917 between the new Bolshevik regime and Russia's imperial past; and how homogenous and how mobile was Soviet society?